Treatment of Hypertensive Cardiogenic Edema with Intravenous High-Dose Nitroglycerin in a Patient Presenting with Signs of Respiratory Failure: A Case Report and Review of the Literature - López-Rivera, Fermín (Am J Case Rep, 2019)
Patient: Male, 63 Final Diagnosis: Hypertensive cardiovenic pulmonary edema Symptoms: Shortness of breath Medication: — Clinical Procedure: — Specialty: General and Internal Medicine OBJECTIVE: Management of emergency care BACKGROUND: Pulmonary edema is the accumulation of fluid in the lung secondary to increased hydrostatic pressure. Hypertensive cardiogenic pulmonary edema presents with a sudden onset of severe dyspnea, tachycardia, and tachypnea, and can occur when the systolic blood pressure exceeds 160 mmHg in association with acute decompensated congestive cardiac failure (CCF). A case is presented of hypertensive cardiogenic pulmonary edema treated with high-dose nitroglycerin and includes a review of the literature. CASE REPORT: A 63-year-old Hispanic male with a medical history of hypertension, coronary artery disease, heart failure with a reduced ejection fraction of 35%, chronic kidney disease (CKD) and diabetes mellitus, presented as an emergency with acute, severe dyspnea. The patient was initially managed with 100% oxygen supplementation and intravenous (IV) high-dose nitroglycerin (30 mcg/min), which was titrated every 3 minutes, increasing by 15 mcg/min until a dose of 120 mcg/min was reached. After 18 minutes of aggressive therapy, the patient’s condition improved and he no longer required mechanical ventilation. CONCLUSIONS: Hypertensive cardiogenic pulmonary edema is a challenging clinical condition that should be diagnosed and managed as early as possible, and distinguished from respiratory failure due to other causes. Although hypertensive cardiogenic pulmonary edema is usually managed acutely with high-dose diuretics, this case has highlighted the benefit of high-dose IV nitroglycerin, and review of the literature supports this treatment approach.